INTEGRATION OF THE ACCOUNTING INFORMATION SYSTEM AND PRODUCTION ON TIME AND ITS REFLECTION IN REDUCING COSTS - Asst. Lec Hasan Sahab Mutar; Asst. Lec Humam Munaf Raheem; Asst. Lec Mustafa Majeed Hameed AL-bahadle (Scholars Digest Publishing, 2024)
The study aims to know and explain the impact of the integrative relationship between the accounting information system and The just-in-time production system (JIT( and their role in reducing costs and the efficiency of the information provided to the economic unit. The researchers concluded that the application of accounting information systems increases the ability of the economic unit to adapt to developments in the business environment as well. This integrative relationship fundamentally affects the reduction of costs and increases the efficiency of management through the quality of information obtained by the economic unit. which economic units need to carry out their work.
Keywords: Accounting information system, accounting information system requirements, The just-in-time production system, The just-in-time production system requirements, The just-in-time production system strategy.